Spatial analysis and risk factors of dengue hemorrhagic fever in Yogyakarta city, 2017-2018 - Sulistyawati, Sulistyawati; Nur Fatimah, Atin; Aqmarina, Nurma (International Journal Of Community Medicine And Public Health, 2023)
Background: Dengue hemorrhagic fever (DHF) is a public health problem with high morbidity and mortality rates. These diseases are caused by the bite of the Aedes aegypti mosquito. Yogyakarta City is one of the endemic areas of DHF in Indonesia. This study aims to analyze the spatial distribution of DHF incidents and determine the risk factors associated with DHF incidence in Yogyakarta in 2017-2018. Methods: This was a descriptive quantitative with an ecological study design and using secondary data. Data was analyzed using statistical analysis and spatial analysis. Results: Spatial analysis shows that the DHF distribution does not follow the distribution of population density, house density, and larva-free rate. We found the population density (p value= 0.010, r = -0.661), house density (p value= 0.059, r = -0.516), and larva-free rate (p value= 0.907, r= -0.034). Conclusions: Spatially, there is no relationship between population density, house density, and larva-free rate to the DHF incidence in the City of Yogyakarta in 2017-2018. There is a relationship between population density and the incidence of DHF. In contrast, house density and larva-free rate have no association with the incidence of DHF in Yogyakarta in 2017-2018. The higher the population density, house density, and larva-free rate, the tendency for the incidence to decrease.